Influence of Different Pigment Incorporation Methods on the Sorption and Solubility of Medical Silicones - Nobrega, Adhara Smith [UNESP]; De Moraes Melo Neto, Clóvis Lamartine [UNESP]; De Magalhães Bertoz, André Pinheiro [UNESP]; De Melo Moreno, André Luiz [UNESP]; Goiato, Marcelo Coelho [UNESP] (Thieme, 2020)
Objective  The aim of this study is to verify the influence of three pigment incorporation methods (conventional, mechanical, and industrial) on the sorption and solubility of the MDX4-4210 and A-2186 silicones. Materials and Methods  The groups formed were based on the silicones used (A-2186 and MDX4-4210), intrinsic pigments (pink, bronze, and black), and pigment incorporation methods (conventional, mechanical, and industrial). The dimensions of all samples were 45-mm diameter (o) × 1-mm thickness. Readings were taken initially and after 1,008 hours of aging. Statistical Analysis  Three-way analysis of variance and the Tukey's test were performed (α = 0.05). Results  For sorption and solubility, there was no difference between the incorporation methods for the A-2186 silicone, regardless of the pigment used (p > 0.05). For pink MDX4-4210, the industrial and mechanical methods showed higher values of sorption compared with the conventional method (p < 0.05). For bronze MDX4-4210, the industrial method showed a higher sorption value compared with the conventional and mechanical methods (p < 0.05). For black MDX4-4210, there was no difference between incorporation methods based on sorption (p > 0.05). For pink MDX4-4210, the mechanical method showed a higher solubility value compared with the industrial and conventional methods (p < 0.05). For black MDX4-4210 and bronze MDX4-4210, there was no statistically significant difference between incorporation methods based on solubility (p > 0.05). Conclusion  Based on sorption and solubility, for the A-2186 silicone, the conventional, mechanical, and industrial methods of pigment incorporation were equivalent. For the MDX4-4210 silicone, its results of sorption and solubility were varied, and further studies are recommended.
Keywords: A-2186; maxillofacial prosthesis; silicone elastomers; solubility